Wanted : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2011)
Former best friends Hanna, Aria, Spencer, and Emily, who lost their best friend and leader, Alison, years ago when she disappeared, find themselves in grave danger when they pursue the truth about Alison.
Reprint. Originally published: 2010.
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Murder -- Juvenile fiction; High schools -- Juvenile fiction; Friendship -- Fiction; Murder -- Fiction; High schools -- Fiction; Schools -- Fiction; Mystery and detective stories